Existence Results for Nonlinear Boundary Value Problems of Fractional Integrodifferential Equations with Integral Boundary Conditions. (12th February 2009) - Ahmad, Bashir; Nieto, Juan J.
Abstract : This paper deals with some existence results for a boundary value problem involving a nonlinear integrodifferential equation of fractional orderq ∈ ( 1, 2 ] with integral boundary conditions. Our results are based on contraction mapping principle and Krasnosel'skiĭ's fixed point theorem.